Corporate Financial Performance Effects of Macro Economic Factors Against Stock Return - Angrita Denziana; Indrayenti INDRAYENTI; Ferdinan Fatah (Universitas Bandar Lampung (UBL), 2014)
The improvement in macroeconomic factors can provide a signal as a sign that the investment climate will also be more conducive. Indonesia Stock Exchange (IDX) which can be considered as the main indicator of financial performance has experienced substantial growth from 1999 until now. IDX experiencing a record low in 1998 amid the economic crisis, but reversed course and reached record highs in 2013. In 2010 IDX is the index with the best performance in the Asia Pacific region with an increase of 44 percent. This study aims to determine the effect of the company's financial performance with ROA and ROE indicators, macroeconomic factors with indicators of SBI interest rate and exchange rate on stock returns of non-financial companies listed on the Indonesia Stock Exchange. The results of this study indicate that the variable ROA partially negative effect on stock returns, ROE has a positive effect on stock returns, the variable interest rate and exchange rate SBI positive effect on stock returns. Conclusion This study shows that the regression model is formed from Independent variables ROA, ROE, SBI interest rate and the exchange rate can be used as the basis of investment decision making considerations forinvestors in the Indonesia Stock Exchange (IDX) mainly for shares in the company's nonfinance.